Analisis Literasi Mahasiswa Universitas Islam Negeri Sumatera Utara Medan terhadap Pinjaman Online - Aprialdi, Fikri; Dalimunthe, Muhammad (Tapis: Jurnal Penelitian Ilmiah, 2023)
Online Loan is one of the developing financial products in Indonesia. However, many illegal online lending problems are caused by a lack of financial literacy. The purpose of this study is to find out how far the knowledge of UIN North Sumatra students is about online loans and cases experienced by UIN North Sumatra students after using fintech. This study used data collection techniques through interviews, observation, and documentation. In this study, researchers used data validity tests through data triangulation. The data analysis used draws on the Miles and Huberman model. In this study, there were 4 people as informants, consisting of UIN North Sumatra students who had made online loan transactions. The results showed that the positive side of online loans is that the procedure for borrowing money in online-based applications is easier and faster to meet their emergency fund.